Flâneur of the Surreality. Vítězslav Nezval’s Surreal Walks around Prague - Gawarecka , Anna (Poznańskie Studia Slawistyczne, 2020)
In the surrealistic period of his literary work Vítězslav Nezval, following the French formula of presenting Paris as an archetypical modern city, published textual passage Pražský chodec (1938) which title is taken from the famous Apollinaire’s story but its narrative schema resembles the Louis Aragon’s Paris Peasant. In opposition to avant-garde ideas of the perfect urbanization projects connected with the technological progress and futurological utopias Nezval tries to show Prague (more mysterious and surreal in his eyes than the capital of France) as a space of living literary tradition, full of lieux de mémoire and traces of long past events. Walking around urban streets, alleys or bridges often regarded as the typical surrealistic activity, becomes here an instrument of evoking these memories and it is also treated as a metaphor of poetic creation.